LAKBAN (ALAT KONTROL BAGI SOPIR BUS YANG BANDEL) - Asrofi, Mirza; Ma’ruf, Muhamad Irham; Syah, Abdurrahman; Afdhaluddin, Muhammad Hizba; Lesmana, Dony Hendra (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
Driver factor was ranked the first amounting to 93.52% as the main cause of the accident. The negligence of driver who drove over the speed limit specified (reckless). Ministry of transportation has sought to alert passengers to the bus driver put a sticker warning. So, we need a technology that facilitates the ministry of transportation to monitor in real time of the bus driver. Preparation method is based on problems that are applicable. The tool components include GPS, microcontrollers, sirens, GSM module, and server. Accuracy measurement test results the vehicle transfer rate versus time between LAKBAN is that the vehicle speedometer is at 100%.